Land, liberation and prophetic witness: Re-envisioning land justice through Biko’s Black Theology - Jentile, Thembelani E. (Hervormde teologiese studies, 2025)
This article investigates the outstanding question in South Africa of the land, by way of Black Theology, honing in on it the liberative optic of Steve Biko (Stephen Bantu). It argues that today’s post-apartheid land clashes do not engage ordinary politics or law; they involve theological crises that expose the moral bankruptcy of both the Church and South Africa. The article juxtaposes the Reformed ethics of Jacobus Vorster, the eschatological perspective of Kelebogile Resane and the radical emancipatory paradigm of Black Theology with a view to highlight land as neither commodity nor property, but sacred inheritance, communal memory and spiritual root. Biko’s theology is informed by Black consciousness, the memory of ancestry and incarnational practice, which constructs a decolonial Christology that challenges Christian nationalism and spiritual responsibility for land dispossession. The analysis contends against white refugee claims and theological amnesia that reverses justice, arguing for a prophetic voice rooted in remembrance, restitution and ethical impetus. Contribution: It mobilises Biko, Mosala, Vellem and others to (re)imagine an African and African Christian identity by restoring the role of the Church as conscience of the nations. Land justice appears here as a theological imperative, as a site where liberation, self-expression and divine action meet. When people whose land was stolen from them regains that land, it is not, after all, just the land they are reclaiming but their testimony.